Factors that influence foreign direct investment in Malaysia / Siti Noor Farahin Hisammuddin and Nabilah Abdullah - Hisammuddin, Siti Noor Farahin; Abdullah, Nabilah (Faculty of Business and Management, 2016)
This paper analysed factors that influence Foreign Direct Investment (FDI) in Malaysia. Variables that considered are Exchange Rate (EX), Inflation Rate (INF) and Interest Rate (RIR). This study required 33 years data for each variable from year 1982 to 2015. Methodology used in this study is by using Multiple Linear Regression with series data. This method is used to determine the relationship between independent variable and dependent variable. Besides that, Econometric Views 9.0 (E-views) would be used for testing and analysing the data collected. The empirical results have found there is negatively significant relationship between exchange rate and FDI and positively significant relationship among inflation rate and interest rate with FDI. Most of the previous study showed that exchange rate, inflation rate and interest rate have significant relationship with FDI. As guidance from previous study, this research will examine the relationship between factors that influence FDI in Malaysia.